Organización administrativa y funcional en las Instituciones Educativas de la Zona 7 – Distrito Espíndola 11D05, durante el año lectivo 2019 – 2020 - Villamarín Tapia, Luis Fernando (2021)
The present research work called Administrative and functional organization in the Educational Institutions of Zone 7 - Espíndola District 11D05, during the 2019-2020 school year, aims to establish the legal bases of the Administrative and Functional Organization in the educational institutions of the country through the conception of a legal framework proposed by the current documentation using a descriptive and correlational study, to successfully arrive at this approach was necessary. First, establish the legal bases of the administrative and functional organization of the institutions, which will be referred to as the legal framework during the literature review. The second moment, analyze the administrative and functional organizational situation of the educational establishments in District 11D05 Espíndola through the application of a data collection instrument, survey, which collects relevant information ending in the third moment with the establishment of correspondence from the compliance with the legal framework established in the participating institutions. Such review for the District institutions has the intention of creating an X-ray of compliance with the regulations issued by the Ministry of Education, additional, being a study that seeks to reach all the educational centers of Espíndola fiscal and fiscal and fiscal authorities in consideration of the regulations. health services following COVID 19 was projected as a quantitative study. A significant contribution to the development was the acquisition of the database with the contacts of all the directors provided by the District Office, which facilitated the application of the survey by virtual means. The data obtained from District 11D05 showed significant efforts in the application of the guidelines issued by the regulatory body of Education in Ecuador, the Ministry of 5 Education, but even with the work carried out, it is necessary to undertake pertinent adjustments in the institutions in relation to infrastructure. However, it is necessary to point out that, regarding human resource management, the compliance rates revealed high percentages. The study that from the beginning sought to determine the status of compliance with the regulations in the educational institutions in the District fulfilled its purpose, in turn questioning the rest of the Districts at the Zone 7 level, leaving the door open with the information collected in this first experience of the expansion of radiography to other areas, reaching a country level